Molecular Characterization of Environmental Non-Tuberculous Mycobacteria Using PCR- RFLP Analysis of 441 Bp Heat Shock Protein 65 Fragments - H Rezaei-Yazdi; N Hoseini; H Fazeli; J Faghri; S Moghim; E Sarikhani; B Nasr-Esfahani (Tehran University of Medical Sciences, 2012)
Background: Non- Tuberculous Mycobacteria are environmental opportunistic pathogens that can be found in various terrestrial and aquatic habitats. There are an epidemiological links between species isolated in tap water and those isolated from patients. hsp65 gene has more variability in its sequences, compared to the some more conserved genes in NTM, for identification of mycobacteria to species level. In this study, the prevalence of NTM in Isfahan City water samples was determined using culture, biochemical tests and PCR-RFLP analyses of hsp65 gene.Methods: Eighty-five water samples were collected and cultured. The mycobacterial isolates were identified by conventional biochemical tests. A 441 bp fragment of hsp65 genes was amplified and digested by two restriction enzymes, BstEII and HaeII. Digested products were analyzed using polyacrilamid gel electrophoresis (PAGE).Results: 25.9% of the water samples contained different species of NTM. Dominant isolates were M. fortuitum (26.7%), M. chelonae like organism (13.3%) and M. mucogenicum (13.3%). Nineteen isolates of Mycobacteria were differentiated using hsp65 genes PCR-RFLP. Three isolates could not be identified at the species level because their RFLP patterns were different from other known PCR-RFLP profiles. There were different hsp65 gene PCR-RFLP profiles produced by digestion with BstEII and HaeIII. Conclusion: This study showed that PCR-RFLP of hsp65 gene in mycobacteria is more reliable method for identification of NTM at the specie level than conventional phenotypic methods (P<0.05). In comparing of RFLP patterns of this study to other investigation, some minor differences were negligible.